CFD Simulations of Pressure Drop in KATAPAK-S Structured Packing (Iranian Journal of Chemical Engineering)
KATAPAK-S is a type of structured catalytic packing, which is used in reactive distillation processes. The dry pressure drop characteristic (the pressure drop in the absence of liquid flow) is of significant importance for the investigation of process hydrodynamics. In this paper, the dry pressure drop within the catalyst packed channels of KATAPAK-S has been investigated using Computational Fluid Dynamics (CFD). Results of the CFD simulations were validated using experimental pressure drop data and empirical correlations. The CFD results showed an excellent agreement with theoretical and experimental data. Keywords: KATAPAK-S structures, Pressure drop, Structured packing, CFD